Optimization of Islamic Religious Education to form The Islamic Character of The Guidance Studio Students in Lorong Sungai Mulia 5 Gombak Kuala Lumpur Malaysia - Ramdani, Johan; Fathoni, Tamrin (Sultan Journal of Social Sciences and Humanities, 2025)
The purpose of this service is to optimize Islamic religious education at the guidance studio of Lorong Sungai Mulia 5 Gombak Kuala Lumpur through creative and contextual learning strategies to form Islamic character and prepare the future of students with noble and competitive character. The ABCD method is used with the Discovery stage to identify individual, institutional, social, and cultural assets through interviews, observations, and FGDs. In the Dream stage, teachers, students, and the community formulated a common dream for the studio to become a center for Islamic character development with interesting and technology-based PAI learning. The Design and Define stages produce concrete programs such as teacher training, curriculum development, religious activities, parenting classes, and interactive learning implementations that are evaluated periodically to measure program success and impact. The results of the service showed a significant increase in students' religious knowledge and practices through the PAI strengthening program and the habit of daily worship. Students become more disciplined in congregational prayers, regularly read the Qur'an before studying, and show a polite and responsible attitude independently. This change reflects the success of the program in forming an Islamic character based on faith awareness, not just obedience due to coercion.